2017
DOI: 10.4236/jwarp.2017.912099
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Assessment by Measuring and Using Landsat 7 ETM+ Images for the Current and Previous Trend Perspective: Lake Tana Ethiopia

Abstract: Recently there are signs of water quality impairment in Lake Tana, the largest fresh water in Ethiopia. The lake is the growth corridor of the government and supports millions of livelihood around. In order to sustain the benefit and maintain the ecosystem of the lake, the lake health has to be kept safe. Therefore monitoring and evaluation of the water quality of lake is very vital. This study focuses on current and previous trends water quality of the lake through measurements and Landsat Images near entry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…The available phosphorus concentrations in the lake bottom sediments were not related to any other measured parameter ( Table 1), indicating that the conversion processes that caused the pattern are unique. We should note that Gumara and Rib rivers that enter the lake on the east side have during the rainy season a dissolved P concentration that exceeds the lake concentration [27,30,47,66]. In the Awramba watershed close to lake outlet, the concentration was about three to four times the observed average dissolved phosphorus content in the lake of 0.18 mg L −1 [26,66].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The available phosphorus concentrations in the lake bottom sediments were not related to any other measured parameter ( Table 1), indicating that the conversion processes that caused the pattern are unique. We should note that Gumara and Rib rivers that enter the lake on the east side have during the rainy season a dissolved P concentration that exceeds the lake concentration [27,30,47,66]. In the Awramba watershed close to lake outlet, the concentration was about three to four times the observed average dissolved phosphorus content in the lake of 0.18 mg L −1 [26,66].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the nutrient input from the upland agricultural areas has increased [26,46]. Phosphorus concentrations in the lake water have been rising [47] and have resulted in a progressive change of the lake from mesotrophic to eutrophic status [31].…”
Section: Study Areamentioning
confidence: 99%
“…ese conventional methods are more precise, but they are carried out with limited water samples over space and time, thus may not reflect the overall lake water quality [4]. ey are not only limited in their spatial and temporal coverage but also timeconsuming and expensive [4][5][6][7][8][9]. In this paper, site-specific relationships are developed for mapping suspended sediment concentration (SSC), turbidity, and Secchi disc depth on Lake Tana.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, a number of studies have demonstrated that suspended matter distribution in inland waters can be mapped from various types of satellite remote sensing data, such as Landsat TM, Landsat ETM+, and Landsat-8, Moderate Resolution Imaging Spectroradiometer (MODIS), Medium Resolution Imaging Spectrometer (MERIS), Advanced Very High-Resolution Radiometer (AVHRR), Sea-Viewing Wide Field-of-view Sensor (SeaWiFS), and Satellite Pour I'Observation de la Terre (SPOT) [4][5][6][7][8][9]11]. Previous studies have proposed Landsat-7 ETM+ and Landsat-8 bands as a spectral self-phase modulation (SPM), turbidity, and Secchi disc depth (SDD) indicator for Lake Tana [5,8], but its limitation on the temporal resolution is insufficient for the study of dynamic changes of sediment. Kaba et al [7] used Terra-MODIS to investigate the relationship between water quality parameters and Terra-MODIS derived reflectance only at Gumara river inlet to Lake Tana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation